A single-step DNAzyme sensor for ultra-sensitive and rapid detection of Pb2+ ions. (1st February 2021) - Meng, Jiyu; Huang, Jiamei; Oueslati, Rania; Jiang, Yu; Chen, Jiangang; Li, Shanshan; Dai, Shijie; He, Qiang; Wu, Jayne
Abstract: Effective protection from Pb 2+ contamination calls for its rapid detection in environmental and biological samples, including water sources. This work demonstrates a rapid, highly sensitive and specific DNAzyme-based Pb 2+ biosensor, which is also the first reported label free bioelectronic sensor for catalytic hydrolysis. The sensors are prepared from gold-plated interdigitated electrodes (IDEs), functionalized with oligonucleotide substrate strands and subsequent hybridization with DNAzyme strands. After sample fluid is applied onto a sensor for detection, the sensor's serial capacitance is continuously interrogated by an optimized alternating current (AC) signal for 15 s. If Pb 2+ is present, the DNAzyme catalyzes a cleavage reaction of the substrate, releasing the DNAzyme and substrate fragments into the solution. The reaction leaves partial substrate strand at the sensor surface, causing a change in the IDEs' interfacial capacitance. Another novelty here is that capacitance measurement simultaneously induce a fluidic enrichment effect, AC electrothermal effect, thus concentrating and measuring Pb 2+ in a single step. The AC signal is carefully optimized to minimize non-specific collection of macromolecules, including released DNAzyme and substrate fragments. In this work, Pb 2+ level can be quantified in 15 s with a detection limit of 1.26 fM and a linear dynamic range from 1 fM to 1 pM in analytical buffer. To demonstrate the sensor's specificity, non-target metal ions are tested, all giving negligible responses. Testing of tap water samples collected under different conditions also yields reasonable results, validating the robustness of this sensor. This rapid and sensitive sensor holds high promise for on-site detection of Pb 2+ in practical samples.